(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2008)
The article is devoted to the problem of generation of cement-soil out of loamy clay occurring in the territory of Abaqabad City (Iran). As a result of implemented laboratory tests, it turned out that temporary resistance of maximum pressure is obtained in the case of 7% cement, when humidity is 2% lower then optimum humidity of sample soil. The standard stability of cement-soil with this optimum mixture and humidity is determined after 28 days and it makes up 5․07 MPa, which is only a part of its stability. Particularly, the stability of test soil increases up to 6․07 MPa at 60 days of drying.